Serum Galactomannan: A Predictor of Poor Outcomes in Peritoneal Dialysis Patients With Fungal Peritonitis - Talerngsak Kanjanabuch; Tanawin Nopsopon; Thunvarat Saejew; Athiphat Banjongjit; Pongpratch Puapatanakul; Somkanya Tungsanga; Jakapat Vanichanan; Sajja Tatiyanupanwong; Kanjana Tianprasertkij; Worapot Treamtrakanpon; Uraiwan Parinyasiri; Kamol Khositrangsikun; et al. (Kidney International Reports)
Introduction: The potential value of serum galactomannan index (GMI) in monitoring treatment response in patients with fungal peritonitis who are receiving peritoneal dialysis (PD) was assessed in the present study. Methods: The study included all Thailand fungal PD-related infectious complications surveillance (MycoPDICS) DATA study participants who had timely PD catheter removal and availability of both baseline and ≥2 subsequent serum GMI measurements after starting antifungal therapy (if available). Serum GMI was assessed by direct double-sandwich enzyme-linked immunosorbent assay with reference to positive and negative control samples. Comparisons of categorical variables among groups were analyzed by Fisher’s exact test for categorical data and the Wilcoxon rank-sum test for continuous variables. Mortality outcomes were analyzed by survival analyses using Kaplan-Meier curves with Log-rank test. Results: Seventy-six (46%) of 166 participants from 21 PD centers between 2018 and 2022 were included. The median age was 58 (50–65) years, and a half of the patients (50%) had type II diabetes. Nineteen (25%) and 57 (75%) episodes were caused by yeast and mold, respectively. Death occurred in 11 (14%) patients at 3 months, and no differences were observed in demographics, laboratories, treatment characteristics, or in baseline serum GMI between those who died and those who survived. Serum GMI progressively declined over the follow-up period after the completion of treatment. Patients who died had significantly higher posttreatment serum GMI levels and were more likely to have positive GMI after treatment. Conclusion: Serum GMI is an excellent biomarker for risk stratification and treatment response monitoring in patients on PD with fungal peritonitis.